Hybrid photocatalyst for seawater purification : catalyst composition - Weerana, Eh Kan (2014)
Hybrid photocatalyst of Titanium Dioxide (TiO2) catalyst become an attractive alternative promoter for seawater purification. The effect of catalyst composition in the seawater purification via photocatalytic reaction was investigated. Synthesis of a highly active solid catalyst is investigated by loading the different weight ratio of TiO2 on activated palm oil fiber ash through wet impregnation technique. The prepared catalysts were characterized by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Brunauer Emmett Teller (BET). The catalyst was tested with seawater (weight ratio of catalyst to seawater of 1:400). The experiment was conducted in a 1 L Borosilicate photoreactor and mercury light with 365 nm wavelength was used. The performance of the catalyst was tested for two hours. The Chemical Oxygen Demand (COD), pH, Conductivity, Turbidity, Biochemical Oxygen Demand (BOD), Total Dissolved Solid (TDS) and Dissolved Oxygen (DO) of the seawater was analysed prior and after the testing. Better quality of water was obtained. SEM images show that the fiber ash became a good supporter for TiO2. TiO2 was well dispersed on fiber ash surface after the impregnation. BET indicates that the catalyst pore structure was mesoporous. The XRD result also indicates that the TiO2 has anatase crystal while fiber ash has quartz crystal. The solid solution might form too. The weight ratio of fibre ash to TiO2 of Ti:Ash 50:50 were found to be the most effective catalyst in purification of seawater by reducing 10.86% of salt concentration. In conclusion, the photocatalysis process is able to provide an alternative effective treatment for seawater purification